2011
DOI: 10.1007/s11103-011-9784-y
|View full text |Cite
|
Sign up to set email alerts
|

Modification of reactive oxygen species scavenging capacity of chloroplasts through plastid transformation

Abstract: Reactive oxygen species (ROS), including superoxide anions, hydrogen peroxide and hydroxyl radicals are generated through normal biochemical processes, but their production is increased by abiotic stresses. The prospects for enhancing ROS scavenging, and hence stress tolerance, by direct gene expression in a vulnerable cell compartment, the chloroplast, have been explored in tobacco. Several plastid transformants were generated which contained either a Nicotiana mitochondrial superoxide dismutase (MnSOD) or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 60 publications
1
23
2
Order By: Relevance
“…These combinations were of interest since DHAR and GR catalyze consecutive steps in the ascorbate-glutathione cycle in chloroplasts, and combining expression of GR and GST together could significantly influence glutathione homeostasis, further affecting the ROS-scavenging capacity of the chloroplast. As has already been described in detail (Le Poage et al 2011), Southern blot analysis confirmed integration of the foreign genes, and Western blot analysis confirmed expression of the relevant transgenes in leaf tissue. The transplastomic lines showed the predicted altered activity of the relevant enzymes (threefold increase in SOD activity, up to threefold increase in DHAR activity, up to sixfold increase in GR activity, twofold increase in both GST and GPX as a result of insertion of the GST gene, up to fourfold increase in DHAR/GST, and fivefold increase in GR in the double transformants) and of the redox state of ascorbate and glutathione.…”
Section: •ϫsupporting
confidence: 79%
See 3 more Smart Citations
“…These combinations were of interest since DHAR and GR catalyze consecutive steps in the ascorbate-glutathione cycle in chloroplasts, and combining expression of GR and GST together could significantly influence glutathione homeostasis, further affecting the ROS-scavenging capacity of the chloroplast. As has already been described in detail (Le Poage et al 2011), Southern blot analysis confirmed integration of the foreign genes, and Western blot analysis confirmed expression of the relevant transgenes in leaf tissue. The transplastomic lines showed the predicted altered activity of the relevant enzymes (threefold increase in SOD activity, up to threefold increase in DHAR activity, up to sixfold increase in GR activity, twofold increase in both GST and GPX as a result of insertion of the GST gene, up to fourfold increase in DHAR/GST, and fivefold increase in GR in the double transformants) and of the redox state of ascorbate and glutathione.…”
Section: •ϫsupporting
confidence: 79%
“…This laboratory has introduced genes encoding manganese SOD (MnSOD), DHAR, GR, and GST (with GPX activity) into the tobacco chloroplast genome (plastome) to obtain transplastomic lines, as has been previously described Poage et al 2011). Double transplastomic lines expressing DHAR and GR (DHARϩGR) or GR and GST (GRϩGST) were also obtained (Le .…”
Section: •ϫmentioning
confidence: 99%
See 2 more Smart Citations
“…integration and expression of transgenes into the chloroplast genome) can directly increase the activity of several ROS scavenging enzymes in this organelle, resulting in both altered levels and redox states of metabolites (ascorbate and glutathione) and modified response to abiotic stresses. Poage et al (2011), also showed a diminished impact of UV-B radiation on relative variable fluorescence in transformants expressing either superoxide dismutase (SOD) or glutathione reductase (GR) in their chloroplasts. However, the most pronounced effects of abiotic stress (chilling, salt and methyl viologen-induced oxidative stress) were observed in double transformants ) expressing either dehydroascorbate reductase (DHAR) and glutathione reductase (GR), or gluathione reductase and glutathione-S-transferase (GST).…”
Section: Introductionmentioning
confidence: 99%